Analysis of the quality of life and burden of family caregivers of elderly people assisted by home care (Research, Society and Development, 2022)
Objective: to analyze the variables that affect the worsening of the quality of life and the increase in the burden among family caregivers of dependent elderly people assisted by a public home care service. Methodology: a cross-sectional, quantitative study carried out with 143 family caregivers of the elderly, between September 2017 and August 2019. Data collection and analysis took place using a sociodemographic, economic and clinical questionnaire, and the Zarit Burden Interview (overload) and World Health Organization Quality of Life-BREF (quality of life) scales. Descriptive analysis was performed, as well as comparison statistics. Results: Most were women (87.4%), with moderate burden (41.8%) or moderate to severe (35.0%), average quality of life, sick (68.5%), with frequent pain (52.4%), who used continuous medication (61.5%), including analgesics (55.2%) and anxiolytics/antidepressants (25.2%), with sleep problems (76.9%), walking (37.8%) and financial (35.7%), who did not perform physical activities (81.8%) and leisure activities (76.9%) and had little social support. In the comparison tests, it was evidenced how these variables had an impact on a decrease in physical, emotional, social and environmental quality of life, and on an increase in overload.Conclusion: It is essential to pay close attention to the physical, psychological, social and environmental needs of family caregivers, to devise strategies that aim to involve other family members, society, health services and public authorities for the inclusion of family caregivers in the care plan.